Identification of novel biomarkers in recurrent / chemoresistant ovarian cancer - Laios, Alexandros (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2009)
The aim of this study was to identify novel biomarkers in recurrent/chemoresistant ovarian cancer, yet an incurable disease. Using cDNA microarrays, we identified distinct patterns of gene expression between primary and recurrent ovarian cancers from different patients with the same histology and from same patients with different histology. Selected targets were validated and correlated with microarray results. Signatures from both cohorts were interrogated against each other and also validated against an independent set of serous papillary ovarian adenocarcinomas. Notably, upregulated genes in the recurrent compared to primary tumours in both cohorts, segregated in the same gene families. Our data propose an integrative model for recurrence in ovarian cancer, in which tumour cells during relapse produce adhesion molecules to mediate attachment, cytokines and inflammatory mediators to stimulate survival and a variety of growth factors bound to their cognate receptors to fully proliferate in order to confront and modulate their immediate environment. Some of the mechanisms involved in recurrence could be specific to the drugs used.
Keywords: Histopathology and Morbid Anatomy, Ph.D.; Ph.D. Trinity College Dublin